A new hybrid of Origanum (Lamiaceae) from the Aegean Island of Karpathos (Dodecanese, Greece): Origanum × karpathicum - Cattaneo, Cristina; Dimarchou, Theocharoula; Özcan, Taner; Di̇rmenci̇, Tuncay (Phytotaxa, 2022)
This study aims to describe a new hybrid of Origanum, which occurs on Karpathos (Greece), by examining its morphology and molecular structure. Nuclear ribosomal DNA (ITS) data of the alleged hybrid specimens, and its putative parents, O. onites and O. vetteri, were examined. Hybrid and parent individuals sharing the same location with the new hybrid from Karpathos and different specimens belonging to ancestral taxa from Turkey, were used for molecular analysis. According to molecular data, there are some polymorphic nucleotide regions showing the hybridization evidence between the new hybrid and its parents. Molecular results show that the new hybrid is more similar to O. vetteri. Also, the new hybrid has some intermediate morphological characteristics ranging between its parents. Consequently, it was deemed appropriate to present the studied putative hybrid to the scientific world as a new hybrid taxon.